1999
DOI: 10.1242/jcs.112.17.2983
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the small GTPase Cdc42 by the inflammatory cytokines TNFα and IL-1, and by the Epstein-Barr virus transforming protein LMP1

Abstract: Cdc42, a Rho-family GTPase, has been implicated in several signal transduction pathways, including organization of the actin cytoskeleton, activation of the c-Jun N-terminal MAP kinase (JNK) and stimulation of the nuclear transcription factor kappa B (NF(kappa)B). We report here that exposure of fibroblasts to the inflammatory cytokines tumor necrosis factor (alpha) (TNF(alpha)) and interleukin-1 (IL-1) triggers the activation of Cdc42 leading first to filopodia formation and subsequently to Rac and Rho activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The activation of Cdc42 by TNF- has been implicated in the regulation of endocytosis and induction of actin polymerization (32,33). Filopodia formation has been proven to be an effective means to monitor the activation of Cdc42 (32,33). We showed that TNF- induced the formation of filopodia in RAW 264.7 cells (Fig.…”
Section: Evs Transport Odn and Induce Tnf- Release And Cdc42 Elevationmentioning
confidence: 71%
See 1 more Smart Citation
“…The activation of Cdc42 by TNF- has been implicated in the regulation of endocytosis and induction of actin polymerization (32,33). Filopodia formation has been proven to be an effective means to monitor the activation of Cdc42 (32,33). We showed that TNF- induced the formation of filopodia in RAW 264.7 cells (Fig.…”
Section: Evs Transport Odn and Induce Tnf- Release And Cdc42 Elevationmentioning
confidence: 71%
“…To gain further mechanistic insights, we used FITC-phalloidin to stain actin and examined its morphology to evaluate the activation of Cdc42. The activation of Cdc42 by TNF- has been implicated in the regulation of endocytosis and induction of actin polymerization (32,33). Filopodia formation has been proven to be an effective means to monitor the activation of Cdc42 (32,33).…”
Section: Evs Transport Odn and Induce Tnf- Release And Cdc42 Elevationmentioning
confidence: 99%
“…From the biochemical perspective, Ras-related superfamily of small GTPases can trigger the formation of actin-based structures (Nobes and Hall 1995, Tapon and Hall 1997, Hall 1998). Correspondingly, numbers of viruses can control over the formation of actin-rich filopodia through modulating Rac, Rho, Cdc42, which in turn enhance virus uptake (Ohta et al 1999, Puls et al 1999, Smith et al 2008, Zamudio-Meza et al 2009, Nikolic et al 2011, Taylor et al 2011, Xiang et al 2012, Freeman et al 2014, Chang et al 2022, Hunziker et al 2022). Recent study reported that SARS-CoV-2 infection induces the upregulation of actin cytoskeleton via the kinase effectors of Rho GTPases (Liu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Cell shape and cell motility are controlled by small GTPases of the Rho family. These proteins are critical regulators of the dynamic reorganization of the actin cytoskeleton [ 101 , 102 , 103 ]. They control cell architecture, focal adhesion complexes and local contraction by promoting the generation of stress fibers or membrane protrusions such as lamellopodia or filopodia [ 104 ].…”
Section: Cytoplasmic Functions Of Ciap1mentioning
confidence: 99%
“…Accordingly, cIAP1 −/− fibroblasts display an enhanced ability to migrate and exhibit filopodia. TNFα has the ability to induce cdc42 activation and actin reorganisation [ 102 , 103 ]. Upon TNFα stimulation, cIAP1 is recruited to the membrane receptor-associated complex, releasing cdc42 and promoting its activation [ 106 ] ( Figure 4 ).…”
Section: Cytoplasmic Functions Of Ciap1mentioning
confidence: 99%